PERAN BAMBU BETUNG (Dendrocalamus asper) PADA KUALITAS PENGELOLAAN LAHAN - Rudi Hilmanto (Pusbindiklat - LIPI, 2010)
Bamboo has contributed to economic potency and the increase of ecology, so bamboo is widely used by local and non-local community. Objectives of this research is to verify role of bamboo betung (Dendrocalamus Asper)at land quality using method Ring rudihilmanto, but in this research it is focussed only at land element influenced by bamboo betung especially at acidity (pH) and porosity. Method of Ring rudihilmanto constitute method of tree interaction and adaptation. This method depicts environmental elements which can be influenced by population a tree species of phase its growth and development at ecosystem, that is: land, temperature, water, and the other organism. Result obtained by that role of bamboo of betung at ecosystem use method of Ring rudihilmanto had ability 14,29% improve alkalis soil and 12,55% to improve soil porosity. Role of bamboo betung (Dendrocalamus Asper) at land quality repair was different significant at 0,01 level.